Black feminist intellectual activism: a transformative pedagogy at a South African university - Hames, Mary Margaret Philome (African Gender Institute, 2016)
This dissertation engages with critical pedagogic theories and activism from a black feminist perspective. The central argument is that education is not only confined to the formal classroom but also takes place in the most unlikely places outside the classroom. This work is premised on the educational philosophies of liberation, embodiment and freedom of the oppressed and the marginalised. The qualitative research is largely presented as ethnographical research, with the researcher located as both participant in the evolvement of the two educational programmes and as writer of this dissertation. Both educational programmes deal with performance and performativity and aim to give voice to the marginalised bodies and lives in the university environment. The research demonstrates how two marginalised groups claim space on campus through performativity involving the body and voice. In the Edudrama, Reclaiming the P…Word, young black women, via representation of word and body, transform the performance space into one in which the misogynistic and racist gaze is transformed. This feminist theatre is intrinsically related to the feminist political work of reclamation of the black female body, which became invisible and objectified for abuse under colonialism, apartheid and patriarchy. The various feminist elements and processes involved in creating feminist text and theatre are discussed. The praxis involved in these processes is then theorised in terms of critical pedagogy as black feminist intellectual activism. In the case of the lesbian, gay and transgender programme, Loud Enuf, the bodies and voices are used differently in the public campus domain to challenge homophobia. This programme is used to raise awareness about sex, sexuality, sexual orientation and gender identity. This programme is intensely political and challenges ambiguous understandings regarding the notion of equality in South Africa post-1994.